(untitled) (Research, Society and Development, 2025)
Methylmalonic acidemia is an autosomal recessive disease stemming from a rare metabolic disorder caused by a deficiency of the mitochondrial enzyme methylmalonyl-CoA mutase. It can present either in the first days of life or have a later onset. This paper aims to present a clinical case of methylmalonic acidemia in childhood and discuss the importance of considering rare diagnoses in the investigation of challenging clinical conditions. Along with data collection from the patient, a literature review was conducted for subsequent clinical correlation. The patient is a 2-year and 9-month-old mixed-race male, presenting with vomiting, decreased level of consciousness, impaired psychomotor ability, prostration, and signs of dehydration. After numerous hospitalizations, an organic acid quantification test was performed, indicating an altered concentration profile. Subsequently, under the care of medical and nutritional specialists, a genetic panel for treatable diseases was requested, leading to a diagnosis of heterozygosity for a pathogenic variant in the MMUT gene. Treatment was initiated with a nutritionist, including vitamin supplementation and dietary restrictions, and the patient is under follow-up with a pediatric neurologist. The clinical condition is well controlled when dietary guidelines, particularly protein restriction, are followed—otherwise, metabolic decompensation may occur. It is possible to conclude the need to disseminate more information about this pathology to enable increasingly early diagnoses and, consequently, more effective treatments.